Femoral Fracture Repair in a Ferret (Mustela putorius furo) - Camassa, José Arthur de Abreu; Muzzi, Leonardo Augusto Lopes; Kawamoto, Fernando Yoiti Kitamura; Diogo, Camila Cardoso; Muzzi, Ruthnéa Aparecida Lázaro; de Lima, Raquel; Saad, Flávia Maria de Oliveira Borges (Acta Scientiae Veterinariae, 2016)
Background: Ferrets (Mustela putorius furo) are increasingly popular as pets. They require similar medical and surgical care as small animals, and orthopedic lesions are more and more common. Fracture diagnosis is based on history, orthopedic exam, and diagnostic imaging. The preferred treatment for femur fractures is surgery, which has a favorable outcome in the majority of cases. However, surgical fracture repair in ferrets can be challenging due to the small size of the bones. The objective of this paper is to report the surgical repair of a femoral fracture in a ferret using an external skeletal fxation system type IA connected to an intramedullary pin (tie-in confguration). Case: An adult ferret was referred to the veterinary hospital after being stepped on. The ferret was diagnosed with an oblique diaphyseal fracture of the left femur and surgery was recommended. Open fracture reduction was performed with a 1 mm in tramedullary pin (Kirschner wire) placed in a retrograde direction into the proximal bone segment. After fracture reduction, the intramedullary pin was inserted into the distal bone segment. The external skeletal fxator type IA was created by the insertion of a 1.5 mm Schanz pin into the distal diaphysis and another, also 1.5 mm, inserted into the proximal metaphysis, both percuta neously. The three pins were connected externally to an aluminum bar with the aid of three staples to form a tie-in system. Rest and restriction of activity were recommended during the frst month after surgery. The ferret recovered well and, at 120 days, orthopedic and radiographic exams showed complete fracture healing. The implant was removed and no functional changes related to ambulation were observed. Discussion: The orthopedic knowledge applied to ferrets commonly originates in procedures performed on cats and dogs. Overall, the main objective when dealing with fractures is to stabilize the broken bone to allow early ambulation. Due to the location and type of fracture, an external immobilization was contraindicated in this case. A plate was considered, but the small diameter of the femur and the consequent risk of iatrogenic fractures made this option not feasible. Therefore, the external skeletal fxator in a tie-in confguration was selected. This method permitted control of the forces acting on the fracture site and had the advantage of low cost and ease of application and removal. Nevertheless, the vast musculature that covers the femur could hinder the use of the external pins and lead to discomfort. The method has been reported with some changes in ferrets, though with inconclusive results due to lack of follow-up. In the present report, a less rigid method, type I, was used since types II and III have a biplanar confguration and were thus inadequate due to the possible contact between the fxator and the abdominal or inguinal region. The precautions taken during placement of the implant were the same as in cats and dogs since their anatomy follows the same pattern. The implant was rigid, light, and effective, allowing early weight-bearing on the affected limb without discomfort to the patient. As such, the external fxator type IA connected to the intramedullary pin in a tie-in confguration was an effective method for the treatment of the oblique diaphyseal femoral fracture in this ferret. Although it is not the recommended method for this type of fracture in cats and dogs, there were no complications in the ferret, with complete fracture healing and return to function of the affected limb. Since there has yet to be a consensus on the recommended procedures in these animals, reports of this nature are important due to the growing number of ferret patients in veterinary practice. Keywords: ferret, osteosynthesis, bone fxation, repair of fractures.